2021
DOI: 10.1016/j.tipsro.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of skin reactions during proton beam radiotherapy – Patient-reported versus clinician-reported

Abstract: Highlights Radiotherapy is used in the treatment for primary brain tumours. Radiotherapy causes acute and late toxicities where skin reactions are most common. The potential for misreporting of toxicity in specific cases may be significant. Oncologist-reported and patient-reported outcomes of skin reactions are crucial. A combination of PROs and oncologists’ assessments is most accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“… 4 , 5 However, the disease itself and the adverse effects of radiotherapy make skin reactions a common adverse effect after radiotherapy in NPC patients. 17 It has been reported that most NPC patients choose to give up treatment due to their inability to tolerate the pain of complications during radiotherapy, thus affecting the therapeutic effect and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 However, the disease itself and the adverse effects of radiotherapy make skin reactions a common adverse effect after radiotherapy in NPC patients. 17 It has been reported that most NPC patients choose to give up treatment due to their inability to tolerate the pain of complications during radiotherapy, thus affecting the therapeutic effect and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Proton therapy is a painless treatment; the patient can return home and perform daily activities. However, the proton beams promote unavoidable sore, reddened skin [38,39] (called erythema/flushing), hair loss and low body energy.…”
Section: External Beam Radiation Therapymentioning
confidence: 99%
“…A PhD thesis was defended in February 2020 [34]. To date, PCSG has published 8 studies [35][36][37][38][39][40], presented in Table 2. As a result, there is an increase in the number of research projects of PBT based on PROMs.…”
Section: Intermediate Outcomesmentioning
confidence: 99%